2019
DOI: 10.1139/cjpp-2019-0286
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of exercise training and high doses of anabolic steroids on cardiac autonomic modulation and ventricular repolarization properties in rats

Abstract: Several studies have reported that high doses of synthetic anabolic androgenic steroids (AAS) can have serious negative effects on health, including the cardiovascular system. The aim of this study was to evaluate the combined effects of AAS and exercise training on ventricular repolarization and cardiac autonomic modulation in rats. Male Wistar rats were allocated into 4 groups: sedentary rats treated with vehicle, sedentary rats treated with nandrolone decanoate, swimming-trained rats treated with vehicle, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…This was referenced in a case report published by Lichtenfeld et al of an AS user who died of ventricular fibrillation [48]. In 2019, Marocolo et al concluded that AS is associated with cardiac autonomic dysfunction and ventricular repolarization, and reflected an increase in QT interval [49].…”
Section: Sudden Cardiac Death and Asmentioning
confidence: 93%
“…This was referenced in a case report published by Lichtenfeld et al of an AS user who died of ventricular fibrillation [48]. In 2019, Marocolo et al concluded that AS is associated with cardiac autonomic dysfunction and ventricular repolarization, and reflected an increase in QT interval [49].…”
Section: Sudden Cardiac Death and Asmentioning
confidence: 93%
“…Dos Santos et al [ 13 ] supported a relationship between AAS use in athletes and imbalance in autonomic control of both the periphery and the heart. In experimental studies, chronic high-dose AAS administration in rats caused impairment of parasympathetic cardiac modulation, decreased HF power, and HRV [ 9 , 10 , 36 ]. It was supported that cardiac autonomic dysfunction caused by AAS use may induce arrhythmias and sudden cardiac death [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially for the effects of AAS on athletes’ cardiac autonomic nervous system, studies are minimal, and the results are controversial. It is argued that their administration increases the action of the sympathetic nervous system and reduces the vagal tone [ 8 , 9 ]. Thus, an imbalance of the two limbs of the autonomic nervous system occurs, which is proven by the alterations of the heart rate variability (HRV) indices.…”
Section: Introductionmentioning
confidence: 99%